Comparison of EMG activity with dynamic movement and static posture on vibration platform - Kuo, J.-H.; Chang, E. C.; Shiang, T. Y. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The aim of this study is to investigate the difference among dynamic movement and static posture on vibration platform as well as no vibration. For this purpose, six healthy male subjects were recruited in this study. Each subject was instructed to maintain four situations: dynamic movement with vibration (frequency: 40 Hz, amplitude: 1 mm), and no-vibration; static posture with vibration (frequency: 40 Hz, amplitude: 1 mm), and novibration. Result showed statistically significant increase at EMG rms of whole body vibration treatment and EMG rms value of dynamic movement was significantly larger than that of static posture (P<.05). In conclusion, dynamic movement can carry into better effect than static posture in training rectus femoris. Secondly, standing on a vibrating platform in squat-stand movement or half-squat posture elicits higher EMG responses in rectus femoris muscle.